Answer:
(61/7, -47/7)
Step-by-step explanation:
Given: y=2/7 -7
y=-x+2
Rewrite the top equation ( y=2/7 -7
y = -47/7
y = -x + 2
Because both equations are equal to y, we can rewrite it again.
-47/7 = -x + 2
Add x to both sides
x + (-47/7) = 2
Add 47/7 to both sides.
x = 47/7 + 2/1
x = 61/7
As stated in the beginning, y is equal to -47/7
Hope you understand!
Answer:
Step-by-step explanation:
Usimg formula for calculating compound interest.
A = P(1+r/n)^nt
P is the principal =$250
r is the rate = 5%
t is the time = 25years
n = 1/4(compounded quarterly)
Substituting to get the amount A.
A = 250(1+5/25)^25/4
A = 250(1+0.2)^6.25
A = 250(1.2)^6.25
A = 250(3.125)
A = $781.31
Hence the accumulated amount in Jessica's annuity after 25 years is $781.31
Answer:
Seven million two thousand five hundred in standard form is 7002500
I'm not pretty sure but I think it would be y I'm not pretty good with these type of question so don't take my answer correctly but at least we tried I tried like 3 times and I guess I didn't really get it its very confusing but just refer to me as a stand off I'm pushing you to get it right good luck try answering my question on my page please I need to complete it tonight to get extra credit and I'm having a hard time that's why I signed up for brainly,com free for 30 days for my trial. Thank you very much
Answer:
just a
Step-by-step explanation:
because if you do anything times by zero, it is zero.